Impact of magnetic nanofillers in the swelling and release properties of k-carrageenan hydrogel nanocomposites - Daniel-da-Silva, Ana L.
Natural polysaccharides such as -carrageenan are an important class of biomaterials for drug delivery. The incorporation of magnetic nanoparticles in polysaccharide hydrogels is currently being explored as a strategy to confer to the hydrogels novel functionalities valuable for specific bio-applications. Within this context, -carrageenan magnetic hydrogel nanocomposites have been prepared and the effect of magnetic (Fe3O4) nanofillers in the swelling of the hydrogels and in the release kinetics and mechanism of a model drug (methylene blue) has been investigated. In vitro release studies demonstrated the applicability of the composites in sustained drug release. The mechanism controlling the release seems to be determined by the strength of the gel network and the extent of gel swelling, both being affected by the incorporation of nanofillers. Furthermore, it was demonstrated that the release rate and profile could be tailored using variable Fe3O4 nanoparticles load. Thus, this seems to be a promising strategy for the development of drug delivery systems with tailored released behavior.